An electrochemical aptamer-based biosensor targeting Plasmodium falciparum histidine-rich protein II for malaria diagnosis - Lo, Young; Cheung, Yee-Wai; Wang, Lin; Lee, Megan; Figueroa-Miranda, Gabriela; Liang, Shaolin; Mayer, Dirk; Tanner, Julian Alexander (Biosensors & bioelectronics, 2021)
Malaria is an infectious disease caused by parasitic protozoans from the genus Plasmodium, with the species P. falciparum causing the highest number of deaths worldwide. Rapid diagnostic tests (RDTs) have become critical in the management of malaria, but current RDTs that detect P. falciparum are primarily antibody-based, which can have drawbacks in cost and robustness. Here, we report the development of an electrochemical aptamer-based (E-AB) biosensing alternative. Through selective evolution of ligands by exponential enrichment, we identify DNA aptamers that bind specifically to P. falciparum histidine-rich protein II (PfHRP2). The aptamer is modified with a methylene blue reporter and attached to a gold sensor surface for square-wave voltammetry interrogation. Through this method we are able to quantify PfHRP2 in human serum with an LOD of 3.73 nM. We further demonstrate the biosensor is stable in serum buffers and reusable for multiple detection rounds. These findings provide a promising alternative to conventional PfHRP2 detection for malaria diagnosis, while also expanding the capabilities of E-AB biosensors. •New DNA aptamers were selected against the malaria biomarker Plasmodium falciparum histidine rich protein 2 (PfHRP2).•Aptamer binding kinetics was rigorously characterized by surface plasmon resonance.•An electrochemical aptamer-based biosensor for reusable detection of the protein target was demonstrated.•PfHRP2 was detected with a detection limit of 3.73 nM.